2011
DOI: 10.1002/wcc.117
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and the imagination

Abstract: This review article surveys the complex terrain of the imagination as a way of understanding and exploring the manifestations of anthropogenic climate change in culture and society. Imagination here is understood as a way of seeing, sensing, thinking, and dreaming that creates the conditions for material interventions in, and political sensibilities of the world. It draws upon literary, filmic, and creative arts practices to argue that imaginative practices from the arts and humanities play a critical role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(121 citation statements)
references
References 71 publications
(79 reference statements)
0
117
0
4
Order By: Relevance
“…Recently, some authors have suggested that climate (also speculative) fiction can play a role in societal transformation processes (Yusoff and Gabrys, 2011), but so far there is neither a theory nor empirical evidence to support this argument. There has been little attention in the social sciences to the role of art and (popular) culture in political processes of change, leaving a significant knowledge gap concerning the ways in which art does and can affectpossibly support -societal change.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some authors have suggested that climate (also speculative) fiction can play a role in societal transformation processes (Yusoff and Gabrys, 2011), but so far there is neither a theory nor empirical evidence to support this argument. There has been little attention in the social sciences to the role of art and (popular) culture in political processes of change, leaving a significant knowledge gap concerning the ways in which art does and can affectpossibly support -societal change.…”
Section: Research Articlementioning
confidence: 99%
“…Imagination requires time and space -literally, places where people can interact to think and talk about the future. Political, economic or scientific Institutions can create these conditions, and deploy "techniques of futurity" (Yusoff and Gabrys, 2011) in support of developing new ideas about possible and desirable futures. Different institutions can do so in different ways, leveraging their convening power (e.g., networks), their expertise (e.g., scientific knowledge), or their financial resources to design imagination processes.…”
Section: Structure and Agencymentioning
confidence: 99%
“…A wide range of literature on the production and circulation of climate science on public stages has been emerging (Yusoff & Gabrys 2011), examining for example the place of film (Svoboda 2016 …”
Section: Conferencementioning
confidence: 99%
“…Climate science, however valuable and important it may be, in and by itself lacks the cultural reflexivity to examine such imaginaries (Yusoff and Gabrys, 2011). Gaonkar (2002) defines a social imaginary as an 'enabling but not fully explicable symbolic matrix within which people imagine and act as world making collective agents', and Jessop (2009: 344) refers to an economic imaginary as 'the semiotic system that gives meaning and shape to the economic field'.…”
Section: Imaginaries and Social Imaginary Significationsmentioning
confidence: 99%